How Does Economics Approach Nature? - Kutasi, Gabor (Cognitive Sustainability, 2022)
Ecological economics exists in relative isolation among the economics disciplines. This is mainly due to the difficulty which economics has in digesting the thought that the ecosystem as an entity can exist independently of human society, since the mentality of economics is based on individual utility and economic efficiency. However, the ecosystem can be integrated into the mainstream New Keynesian model, as it has been demonstrated in practice. Applying modern models, this study explores why it is difficult to change the usual approach to Nature in economics. It also examines how far the ecosystem and economics can interlock.